La eficacia del derecho a recurrir en el recurso extraordinario de revisión - Moreno Alvarez, Fanny Raquel (2023)
ABSTRACT: A new vision has come to administrative law through the high range of citizens' rights in neo-constitutionalism. In this sense, article 66, numeral 23 of the Constitution of the Republic of Ecuador, allows the exercise of the right to address petitions to the authorities and receive a reasoned response. According to Article 76, the numeral seven and literal m of the constitutional text mention the right to appeal the resolution to decide on the person's legal situation. The Constitution prevails over any other standard due to the protection of the hierarchical order of applying the norms. However, the Article 234 of the Organic Administrative Code establishes that if, within the term, there is no response to the extraordinary appeal for revision, it is understood as rejected. It means that it allows the absence of a favorable or unfavorable response, which is why it is contrary to the provisions of the Constitution. The researcher considered the dogmatic, historical-logical, legal, and inductive comparison methodology to accomplish the objectives set through a critical, legal, and doctrinal analysis of the effectiveness of the right of appeal in the appeal—extraordinary review since it is possible to evidence the state discretionally. Based on the results, the researcher established the inaction of the Public Administration in the exceptional appeal constitutes a violation of the right of appeal, legal certainty, the right to petition, and to obtain a reasoned response.